Pendidikan Islam Ramah Budaya: Pendekatan Filosofis - Muhamad Turmuzi; Fatia Inas (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2020)
Lately, the emergence of various problems in human life, especially in education. One of the issues or issues that are quite viral in this modern era is the fragility or in other words the shifting of Islamic values about tolerance towards all tribes and cultures. Therefore, the presence of this study aims to examine how the concept of Islamic education in overcoming various human problems or in the term